2021
DOI: 10.2147/opth.s295769
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early- and Late-Onset NMOSD-Related Optic Neuritis in Thai Patients: Clinical Characteristics and Long-Term Visual Outcomes

Abstract: Objective To compare demographic data, clinical and radiological characteristics, treatments, and long-term visual outcomes between patients with late-onset neuromyelitis optica spectrum disorder-related optic neuritis (LO-NMOSD-ON) (age at onset ≥ 50 years) and patients with early-onset neuromyelitis optica spectrum disorder-related optic neuritis (EO-NMOSD-ON) (age at onset < 50 years). Patients and Methods This retrospective study included 47 patients (69 eyes) who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The latest EDSS score was 2.5 (1.1–4.9) in the REO-NMOSD group and 4.0 (3.0–6.9) in the RLO-NMOSD group after about 5 years of follow-up. Unlike the previous study ( 29 ), the severity of visual acuity showed no between-group differences no matter at onset or the nadir status. However, patients with RLO-NMOSD suffered from more serious sequelae than patients with REO-NMOSD.…”
Section: Discussioncontrasting
confidence: 97%
“…The latest EDSS score was 2.5 (1.1–4.9) in the REO-NMOSD group and 4.0 (3.0–6.9) in the RLO-NMOSD group after about 5 years of follow-up. Unlike the previous study ( 29 ), the severity of visual acuity showed no between-group differences no matter at onset or the nadir status. However, patients with RLO-NMOSD suffered from more serious sequelae than patients with REO-NMOSD.…”
Section: Discussioncontrasting
confidence: 97%
“…However, it has been encountered among children and older adults as well. 6 Interestingly, in the majority of LO-NMOSD, the initial presentation is concomitant with findings of myelitis rather than ON. 14 Fundus examination in NMOSD is usually unremarkable.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Furthermore, Papathanasiou et al 5 found that older age at the onset of NMOSD is a predictor of poor outcome, and patients with LO-NMOSD were expected to reach higher Expanded Disability Status Scale score during follow-up compared to those with early onset NMOSD (EO-NMOSD). Thongmee et al 6 indicated that patients with LO-NMOSD-ON had significantly worse nadir VA at ON onset as well as worse final VA compared to patients with EO-NMOSD-ON. There is no evidence that there is an arbitrary cut-off age at onset, rather clinical phenotypes and disability gradually change with time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation